The Development of Instructional Model According to Immersive Learning in Virtual Reality Environment to Enhance Tour Guide Students’ Oral Communication Ability - Zimin , Zhang; Watannanimtgul , Wirot; Intarasompun , Wichian; Iamsa-ard , Areewan (Journal of Roi Kaensarn Academi, 2023)
The objectives of this research are: 1) to investigate the status of oral communication skills of undergraduate tour guides in Hezhou University and the views of professional teachers based-on immersive-learning teaching model in the virtual environment; 2) to develop the immersive-learning teaching model(PIE) in the virtual reality environment; 3) to implement the course teaching experiment and to evaluate the efficiency of the PIE teaching model. This research instruments includes 1) questionnaire on oral expression skills of undergraduate tour guides; 2) questionnaire on oral communication teaching model of professional teachers; 3) development documents of teaching model, use instructions, virtual scenic spot guide explanation teaching plan, virtual accompany service guide teaching plan; 4) pre-test and post-survey questionnaire of oral communication skills of undergraduate tour guides. Research data collected were analyzed by statistical measures such as percentage, mean, standard deviation, t-test values, and p-values. The study finds that the overall performance of tour guide oral communication skills is moderate at Hezhou University. The sample population t-test results also show that the PIE teaching model is significant for enhancing the undergraduates tour guide oral communication skills with t-test(= 65.56 to 80.33, t=14.80, p=.000).